Size Changeable Nanocarriers with Nuclear Targeting for Effectively Overcoming Multidrug Resistance in Cancer Therapy. (24th September 2015) - Guo, Xing; Wei, Xiao; Jing, Yuting; Zhou, Shaobing
Abstract : A size changeable polymer micelle system with a dual shell, which increases in size under acidic pH conditions and is altered to smaller micelles, triggered by intracellular glutathione (GSH), is successfully developed. It is capable of direct delivering anticancer drugs to the nucleus of multidrug resistance (MDR) tumor cells for highly effective combating of drug resistant breast cancer.